Digital Twin-Driven Operando Monitoring of Electronic Structure Reconstruction in Transition Metal Oxide Electrocatalysts (International Journal of Artificial Intelligence Engineering and Systems, 2026)
The rational design of transition metal oxide electrocatalysts for sustainable energy conversion demands a mechanistic understanding of dynamic electronic structure reconstruction under operating conditions, yet the experimental platforms for capturing such transient phenomena remain fragmented and profoundly underdetermined by static post-mortem analysis. This paper proposes a large-scale research infrastructure that interweaves digital twin architectures with high-throughput operando spectroscopy to achieve continuous, in silico–in situ coupling of catalyst electronic evolution. We establish a system framework in which multi-modal synchrotron-based X-ray absorption and emission data streams are ingested by a continuously updating computational replica of the electrode–electrolyte interface, enabling real-time inference of oxidation state dynamics, orbital hybridization changes, and the emergence of many-body electronic configurations. The architecture is examined through the lenses of data orchestration, transmission latency, cyber-physical synchronization, and semantic interoperability between experimental beamline control systems and predictive machine learning backbones. We dissect structural trade-offs between model fidelity and computational tractability, and outline governance protocols that address data provenance, algorithmic fairness across materials families, and the long-term sustainability of shared digital twin repositories. Particular attention is given to the challenge of capturing rare electronic events—such as the formation of Zhang-Rice singlet states—that decisively influence catalytic turnover but are easily missed in traditional intermittent characterization. By mapping the full lifecycle of operando data onto a digital twin continuum, this work articulates the socio-technical requirements for transforming solitary laboratory discoveries into a federated, robust, and equitable knowledge ecosystem for electrocatalysis, with implications extending to national synchrotron facilities, materials acceleration platforms, and global energy policy frameworks.
Keywords: digital twin, operando spectroscopy, electronic structure, transition metal oxides, electrocatalysis, research infrastructure